Hearing Nature: Approaching International Environmental Communication through Music and Sound - Titus, Olusegun Stephen, Joshua Groffman (The Handbook of International Trends in Environmental Communication, 2021)
This chapter provides an overview of recent work done in the interdisciplinary field of ecomusicology: the study of “music, culture, and nature in all the
Num Pages: 20
Keywords: dept.mus